A novel locking screw hip stem to achieve immediate stability in total hip arthroplasty: A biomechanical study. (October 2015) - Grechenig, Stephan; Gueorguiev, Boyko; Berner, Arne; Heiss, Peter; Müller, Michael; Nerlich, Michael; Schmitz, Paul
Abstract: Introduction: As total hip arthroplasty is now applicable for younger, healthier, and more active patients, bone preservation becomes even more essential, and proximal fixation, resulting in less stress shielding, draws special attention with focus on new strategies and implant designs. Recently, a new type of non-cemented fixation of the femoral component, featured with the locking screw hip (LSH) stem, was developed by Scyon Orthopaedics AG (Au-Waedenswil, Switzerland). The idea to rigidly fix the femoral component of a prosthesis for total hip replacement in this fashion evolved from the very good results achieved with the internal point-contact fixator PC-Fix. The purpose of this study was to investigate the unique characteristics of the LSH-stem and to assess its biomechanical performance in comparison to a conventional cemented prosthesis (Mueller straight stem). Material and Methods: Six paired human cadaveric femora were preserved with the method of Thiel, split in two study groups, implanted with either cemented Mueller straight stem or LSH-stem prostheses and biomechanically tested under progressively increasing axial loading until catastrophic failure. Bone mineral density (BMD) of all femora was evaluated in the femoral head prior to implantation. Axial construct stiffness, failure load and cycles to failure were calculated from the machine data and statistically evaluated at a level of significance p = 0.05. Results: No statistically significant difference between the LSH-stem and the Mueller straight stem was found in terms of axial construct stiffness (2031.5 N/mm ± 483.1 N/mm and 2403.6 N/mm ± 705.2 N/mm, p = 0.115), failure load (4958.8 N ± 1094.1 N and 5907.2 N ± 1562.8 N, p = 0.138) and cycles to failure (7917.7 ± 2188.1 and 9814.3 ± 3125.6, p = 0.138). BMD showed no significant difference between the two study groups, p = 0.616. Conclusion: The LSH-stem seems to be stable enough to carry loads experienced during the rehabilitation period of a patient after THR. Its stability, which is similar to that of the Mueller straight stem, may justify the clinical application of the LSH-stem under thorough investigation.